INTELLIGENT INFORMATION TECHNOLOGIES WITHIN THE FRAMEWORK OF INNOVATIVE EDUCATION MANAGEMENT IN TIMES OF CRISIS - Krasniuk, S.O. (SWorld-Ger Conference proceedings, 2025)
Crisis phenomena — pandemics, military conflicts, economic shocks — place special demands on education systems. In these conditions, it is necessary to move from traditional forms of administration to innovative management, which is based on flexibility,